PERANCANGAN COMPANY PROFILE MUSEUM BATIK PEKALONGAN DALAM BENTUK MULTIMEDIA INTERAKTIF - Tri Maryanto, Raharjo (Arty: Jurnal Seni Rupa, 2015)
Developing batiks that quick at Pekalongan's city less comprehended and acknowledged by a portion Pekalongan's city society own. Commenting that thing Pekalongan's city government builds museum Pekalongan's batik. Museum batiks Pekalongan constitutes museum collection that present information about batik developing at Pekalongan and Indonesian. Base existence field survey museum batiks that intent to give education about batik at Pekalongan less acknowledged by common society because of promotion and information so minim. Leave from that thing, need developed one company profile  museum batiks Pekalongan in forms interactive multimedia with aim increases city society energy Pekalongan and its vicinity to visit museum Pekalongan's batik. In this studi's project is resulted company profile in multimedia's form interactive as media of museum's promotion and information batiks Pekalongan. Interactive Multimedia this gets to be carried on or is accessed by whom just by use of peripheral Personal Computer  (PC) or Laptop. Museum batiks Pekalongan can utilize and utilizes multimedia interactive it utterly to introduce museum Pekalongan's batik to extensive society. Interactive Multimedia this was expected cans be promotion media and tourism guidance that give information about museum batiks Pekalongan so can increase museum's visitor energy batiks Pekalongan.Developing batiks that quick at Pekalongan's city less comprehended and acknowledged by a portion Pekalongan's city society own. Commenting that thing Pekalongan's city government builds museum Pekalongan's batik. Museum batiks Pekalongan constitutes museum collection that present information about batik developing at Pekalongan and Indonesian. Base existence field survey museum batiks that intent to give education about batik at Pekalongan less acknowledged by common society because of promotion and information so minim. Leave from that thing, need developed one company profile  museum batiks Pekalongan in forms interactive multimedia with aim increases city society energy Pekalongan and its vicinity to visit museum Pekalongan's batik. In this studi's project is resulted company profile in multimedia's form interactive as media of museum's promotion and information batiks Pekalongan. Interactive Multimedia this gets to be carried on or is accessed by whom just by use of peripheral Personal Computer  (PC) or Laptop. Museum batiks Pekalongan can utilize and utilizes multimedia interactive it utterly to introduce museum Pekalongan's batik to extensive society. Interactive Multimedia this was expected cans be promotion media and tourism guidance that give information about museum batiks Pekalongan so can increase museum's visitor energy batiks Pekalongan.